Human auditory analyzer system, sound perception and pedagogical approach to its violation. - Dobrotvorskaya Svetlana Georgievna; Sharapova Shakhnoza Murodzhonovna (Genius Journals, 2023)
The auditory analyzer is phylogenetically the most recently formed structure with a complex structure and universal properties.Each of these systems performs a specific function, the violation of which leads to partial or complete hearing loss. This article provides an overview of the adequate impact of the auditory analyzer on the perception of sound. Educators should once again pay attention to the fact that deaf children who do not hear at all are rare. Most children considered deaf have a hard-of-hearing hearing residue, but not a very large one. Sign language teachers should treat such children not as objects of education, but as subjects, that is, as active, acting, surrounding influences.
Keywords: hearing; extrareceptor; eardrum; middle